Numerical modeling and experimental study of plastic strain localization at dynamic loading of samples under conditions close to pure shear - Bilalov, Dmitriy Alfredovich; Sokovikov, Mikhail Albertovich; Chudinov, Vasiliy Valerievich; Oborin, Vladimir Aleksandrovich; Bayandin, Yuriy Vitalievich; Terekhina, Alena Ilinichna; Naimark, Oleg Borisovich (Computational Continuum Mechanics, 2017)
We have studied theoretically and experimentally factors that control plastic strain localization in AlMg6 samples of special shape dynamically loaded during Hopkinson-Kolsky pressure bar tests in a regime close to pure shear conditions. The mechanisms of plastic flow instability are related to collective effects in spatially localized regions. Use of a high-speed infra-red camera CEDIP Silver 450M allowed us to explore the side surfaces of samples in a real-time mode. Mathematical modeling was carried out to investigate the process of plastic shear localization. Numerical calculations associated with the proposed loading scheme were conducted using wide range constitutive equations, which reflect the relation between the mechanisms of structural relaxation caused by the collective behavior of micro-defects and the auto-wave modes of plastic deformation localization. Upon the completion of the test, the microstructural analysis of the samples was performed with an optical microscope-interferometer NewView-5010. The interferometer was also used to carry out the fractal analysis of the surface relief in the areas of intensive deformation localization. After the test, the Hurst exponent, reflecting a correlation between the behavior of defects and the roughness of different scale levels on the sample surface induced by these defects, increases. We have revealed the distinguishing features of plastic deformation that might be associated with the collective scaling behavior of defects producing an abrupt reduction in the relaxation time of stresses, as well as a localized plastic flow. Infrared scanning of the deformation localization region, numerical modeling and subsequent study of the defect structure led to the conclusion that the temperature-softening effects do not play a decisive role in the process of plastic shear localization for the examined material under given loading conditions. One of the mechanisms responsible for this localization is caused by nonequilibrium transitions in the defect ensemble.